The academic production on learning assessment: A view at the studies produced in the field of Scientific Education (Research, Society and Development, 2021)
Learning assessment is a complex field which involves social, educational, political, and related issues, and the way it has been studied and understood in recent decades has changed. In this field, they stand out, from more traditional and objective concepts (somatic evaluation) to concepts that seem to have a more qualitative and procedural character, which aim to (re)plan of teaching and learning processes (diagnostic and formative evaluation). Based on this, our objective is to understand the academic production about the “learning assessment”. Therefore, we consider the theoretical-conceptual contributions of research in Science Education. Qualitative in nature, this article is characterized as a “state of the art” type study. As a tool for collecting information, we use a “Textual Analysis Roadmap” (RAT) and, based on the construction of categories, we characterize the works found in a descriptive-interpretative movement. New articles were found as the focus of investigation, not a subject of interest. This corpus of constitutional analysis was issued for a universe of 768 articles published in the journal “Ciência & Educação” (1998 to 2017). Through the analysis of research, our results are based on the emergence for different concepts about the “learning assessment” in research on Science Education. In addition, we point out that most studies have as their central idea to understand the assessment as an action "part of educational practice".